European Union : Publication of Financial Sector Assessment Program Documentation-Technical Note on European Banking Authority. (IMF Staff Country Reports; Country Report ;, 2013)
This report is an overview of the performance of the European Banking Authority (EBA) against its mandates, given economic conditions prevailing in the banking sector in the European Union (EU). Banks remain a key contributor to the EU financial and professional services industry. Outlook for the sector remains challenging as asset quality has been deteriorating. Priority should be given to increasing its supervisory convergence and quality assurance tasks; regulatory and supervisory actions; and strengthening transparency and the reliability of data.